Metabolic Risk Factors in Calcium Oxalate Stone Formers: A Comparative Analysis with Healthy Control - Khanal, Bikalpa; Jameel, Haris; Syed Rabiullah; Gazder, Tanzeel; Saleh Abo Ali, Farag Mohsen; Hussian, Manzoor (Indus Journal of Bioscience Research, 2025)
Objective: To determine the metabolic abnormalities in the urine of calcium oxalate stone former patients and non-stone formers. Method: A descriptive study was performed in the Department of Urology, SIUT, Karachi, Pakistan, from June 27, 2022, to December 26, 2022. Patients with suspected renal calculi were evaluated, and those confirmed with them had surgical interventions including percutaneous nephrolithotomy, open surgery, or minimally invasive techniques. Stone specimens were examined with infrared techniques. Urine (24-hour) and blood specimens were obtained from 44 patients with calcium oxalate calculi and 51 healthy controls, with serum metabolic parameters evaluated using standard chemical methods. Data were documented electronically. Results: The comparison of metabolic parameters between stone formers and non-stone formers indicated no significant differences in mean urine uric acid levels (415.98 ± 156.51 vs. 366.80 ± 128.52 mg/24 hours, P = 0.096), urine phosphorus (5.84 ± 0.60 vs. 6.19 ± 0.73 mmol/24 hours, P = 0.723), urine oxalate (25.23 ± 15.70 vs. 30.83 ± 28.27 mg/24 hours, P = 0.246), or urine citrate (148.39 ± 113.85 vs. 190.29 ± 151.16 mg/24 hours, P = 0.135). Notable differences were detected in urine magnesium (80.93 ± 33.33 vs. 78.24 ± 39.68 mg/24 hours, P = 0.013) and urine calcium levels (179.02 ± 102.95 vs. 122.02 ± 91.36 mg/24 hours, P = 0.005) between the two cohorts. Conclusion: In conclusion, those with calcium oxalate stones exhibited elevated amounts of magnesium and calcium in their urine relative to those without stones.